Biological Sex Modulates the Adrenal and Blood Pressure Responses to Angiotensin II. Issue 6 (June 2018) - Shukri, Mohammad Zaki; Tan, Jia Wei; Manosroi, Worapaka; Pojoga, Luminita H.; Rivera, Alicia; Williams, Jonathan S.; Seely, Ellen W.; Adler, Gail K.; Jaffe, Iris Z.; Karas, Richard H.; Williams, Gordon H.; Romero, Jose R.
Abstract : The relationship between biological sex and aldosterone on blood pressure (BP) is unclear. We hypothesized that sex would modify the interaction between aldosterone and vascular responses to salt intake and angiotensin II (AngII). To test this hypothesis, in 1592 subjects from the well-controlled Hypertensive Pathotype cohort, we compared responses of women and men to chronic (BP and aldosterone levels in response to dietary salt) and acute (BP, renal plasma flow, and aldosterone responses to AngII infusion) manipulations. Women had a 30% higher salt sensitivity of BP than men ( P <0.0005) regardless of age or hypertension status, a greater BP response to AngII, and a 15% greater aldosterone response to AngII on both restricted and liberal salt diets ( P <0.005). Furthermore, there was an interaction ( P =0.003) between sex and aldosterone on BP response to AngII. Women also had a greater ( P <0.01) increment in renal plasma flow in response to AngII than men. To assess potential mechanisms for this sex effect, we compared aldosterone responses to AngII or potassium from rat zona glomerulosa cells and observed greater aldosterone production in female than male zona glomerulosa cells basally and in response to both agonists ( P <0.0001). In a rodent model of aldosterone-mediated cardiovascular disease induced by increased AngII and low NO, circulating aldosterone levels ( P <0.01), myocardial damage ( P <0.001), and proteinuria ( P <0.05) were greater in female than male rats despite having similar BP responses. Thus, increased aldosterone production likely contributes to sex differences in cardiovascular disease, suggesting that women may be more responsive to mineralocorticoid receptor blockade than men. Abstract : Supplemental Digital Content is available in the text.